Formation of Communicative Competence Through StudentCentered Learning in English Lessons (Eurasian Journal of Learning and Academic Teaching, 2022)
There is no need to prove the value of the foreign language in modern world already. The last years there is an indicative significant increasing of the interest to the foreign language as facility of the international contact. The learner’s miscellaneous age, proceeding with study of the foreign language, first of all, wants to learn to speak on this language. At present sociocultural context of the study of the foreign languages greatly changed: vastly increased their educational and self-educating functions, professional value on the market of the labor. So the primary task of the education foreign language on modern stage is a shaping of the foreign communication competency